Aplikasi Virtual Whiteboard sebagai Media Pembelajaran Daring - Marwa Sulehu; Watty Rimalia; Tamra Tamra (Journal Software, Hardware and Information Technology, 2022)
Government policies in the Pandemi period through the spread of covid 19, authorize schools or university institutions to force online learning (sekolah daring). Due to teachers habit in offline elearning class, utilizing offline learning media such as whiteboard, online learning is very difficult for educators to implement. In other side, online learning can be more effective by utilizing tools that can be used in online learning such as virtual meeting application combined with a virtual whiteboard. Virtual whiteboards will work like contemporary whiteboards but use the educator's monitor screen as the medium for the whiteboard. Virtual whiteboards will assist educators in explaining material that cannot be explained verbally. Teach using Virtual whiteboards are also prior than learning videos i.e. Youtube.com that explain material not interactively. Other pros are Virtual whiteboards can be used in real time and interactively.